2019
DOI: 10.1101/536409
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Re-curation and Rational Enrichment of Knowledge Graphs in Biological Expression Language

Abstract: The rapid accumulation of new biomedical literature not only causes curated knowledge graphs to become outdated and incomplete, but also makes manual curation an impractical and unsustainable solution. Automated or semi-automated workflows are necessary to assist in prioritizing and curating the literature to update and enrich knowledge graphs.We have developed two workflows: one for re-curating a given knowledge graph to assure its syntactic and semantic quality and another for rationally enriching it by manu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Section editors achieved a first selection of 148 papers based on titles and abstracts. After a second review of this set of papers, including full text reviews, a selection of 15 candidate best papers was established 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 . Five reviewers reviewed these pre-selected papers to best four best papers 4 5 6 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Section editors achieved a first selection of 148 papers based on titles and abstracts. After a second review of this set of papers, including full text reviews, a selection of 15 candidate best papers was established 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 . Five reviewers reviewed these pre-selected papers to best four best papers 4 5 6 7 .…”
Section: Resultsmentioning
confidence: 99%
“…The rapid accumulation of new biomedical literature not only causes curated knowledge graphs (KGs) to become outdated and incomplete, but also makes manual curation impractical and unsustainable. Hoyt et al, [11] have developed two workflows to address this issue: the first for re-curating KGs to control syntactic and semantic quality, and the second for rationally enriching KGs through the manually revision of automatically extracted relations for the nodes with low information density. They applied these approaches to the KGs of the NeuroMMSig inventory.…”
Section: Semantic Resources Design Visualization and Curationmentioning
confidence: 99%
“…To the best of our knowledge, this is the first attempt to compare human and machine-curated disease models and examine how the choice of different query constraints in machine approaches can affect disease modeling. Hoyt et al (2019) manually evaluated 2989 statements generated by INDRA using REACH and Sparser readers containing studied genes from MEDLINE abstracts and PubMed Central full-text articles, following which 30.7% of statements were marked as correct, 48.6% required manual correction, and 20.7% could not be corrected. The criterion for correctness was that "all" aspects of the statement, including the subject and object entities, relationship type, phosphorylation, and other post-translational modifications, were extracted to the same extent as careful manual curation could.…”
Section: Related Workmentioning
confidence: 99%
“…The most common error was wrong name entity recognition. Other common errors were the improper assignment of the subject and object, semantic incorrectness due to the presence of a negation word, and errors arising from evidence that did not actually include relations between the subject and object entities [11]. Allen et al (2015) showed that the DRUM system (Deep Reader for Understanding Mechanisms, a version of the general-purpose TRIPS NLP system customized for extraction of molecular mechanisms from biomedical text) has performance (precision and recall) close to human experts in extracting the molecular mechanisms from text, and it was the best performing system among those evaluated.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation